ENDOWMENTS VERSUS RETURNS: COUNTERFACTUAL QUANTILE DECOMPOSITION OF URBAN–RURAL INEQUALITY IN SRI LANKA. Issue 1 (26th April 2013) - De Silva, Indunil
Abstract The main objective of this article is to investigate whether observed urban–rural inequalities in Sri Lanka are due to locational concentration of households with similar endowments that are likely to place them at the bottom of the welfare distribution, or whether it is due to the geographical disparities in the return to these endowments. The study firstly sketches a poverty and inequality profile for Sri Lanka and then identifies the degree to which different levels of endowments and returns effect account for regional welfare differences by applying the Oaxaca–Blinder and Machado–Mata quantile decomposition methods. The study finds in general that, when comparing the urban and rural sectors at the mean, the expenditure differentials are primarily due to differences in returns to endowments. Decomposition results suggest that identical households do not have the same growth prospects independent of where they live, and for geography to play a vital role in explaining the level of household living standards. Quantile regression decomposition estimates suggests that the endowments effect is increasing and dominant for households at the bottom of the welfare distribution, while the returns effect is dominant for wealthier households.